2013
DOI: 10.3389/fonc.2013.00254
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of 14q32 microRNAs in Primary Human Desmoplastic Medulloblastoma

Abstract: Medulloblastoma (MB) is one of the most common pediatric cancers, likely originating from abnormal development of cerebellar progenitor neurons. MicroRNA (miRNA) has been shown to play an important role in the development of the central nervous system. Microarray analysis was used to investigate miRNA expression in desmoplastic MB from patients diagnosed at a young age (1 or 2 years old). Normal fetal or newborn cerebellum was used as control. A total of 84 differentially expressed miRNAs (64 downregulated and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 54 publications
1
11
0
Order By: Relevance
“…MiR-206 expression was found to be downregulated in medulloblastoma tissues belonging to all the four molecular subgroups, as compared to the normal cerebellar tissues. Murine miR-206 expression was also found to be downregulated in SHH subgroup medulloblastomas from Ptch1 (+/−) knockout and Smo +/+ transgenic mouse models that is consistent with reported downregulation of miR-206 expression in desmoplastic medulloblastomas belonging to the SHH subgroup (Lucon et al 2013). MiR-206 expression was also found to be downregulated in all the established medulloblastoma cell lines studied.…”
Section: Discussionsupporting
confidence: 88%
“…MiR-206 expression was found to be downregulated in medulloblastoma tissues belonging to all the four molecular subgroups, as compared to the normal cerebellar tissues. Murine miR-206 expression was also found to be downregulated in SHH subgroup medulloblastomas from Ptch1 (+/−) knockout and Smo +/+ transgenic mouse models that is consistent with reported downregulation of miR-206 expression in desmoplastic medulloblastomas belonging to the SHH subgroup (Lucon et al 2013). MiR-206 expression was also found to be downregulated in all the established medulloblastoma cell lines studied.…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, the unsupervised hierarchical clustering showed two subsets among the tumors, which were based on the relative underexpression of various 14q32 miRNAs (miR‐431, miR‐433, miR‐380, miR‐323a, miR‐329, miR‐543, miR‐1185, miR‐487b, miR‐539, miR‐487a, miR‐485, miR‐668, miR‐154 and miR‐410) in Group 2 as compared to Group 1. The downregulation of 14q32 miRNAs has also been reported in adult GBMs, medulloblastomas and various other cancers such as renal clear cell cancer, breast cancer and ovarian cancer . Earlier studies showed frequent loss of heterozygosity of 14q region, suggesting that allelic deletion on chromosome 14q plays an important role in the pathogenesis of GBM .…”
Section: Discussionmentioning
confidence: 83%
“…The downregulation of 14q32 miRNAs has also been reported in adult GBMs, medulloblastomas and various other cancers such as renal clear cell cancer, breast cancer and ovarian cancer. 38,39 Earlier studies showed frequent loss of heterozygosity of 14q region, suggesting that allelic deletion on chromosome 14q plays an important role in the pathogenesis of GBM. 40 Interestingly, some members of 14q32 cluster especially miR-487b and miR-410 have been shown to discriminate highversus low-risk group in neuroblastoma also.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, expression of ERRg correlates with more favorable clinical outcomes. ERRg expression is linked to progression-free survival in both ovarian and breast cancer [18,23], and is downregulated in prostate cancer cell lines and in medulloblastoma [25,26], indicating that it may play a tumor-suppressing function in these cancers. Similarly, expression of ERRb is decreased in prostate cancer [27].…”
Section: Errs As Cancer Biomarkersmentioning
confidence: 99%